Y balance test: Are we doing it right? - Fusco, A.; Giancotti, G. F.; Fuchs, P. X.; Wagner, H.; da Silva, R. A.; Cortis, C. (Journal of Science and Medicine in Sport, 2020)
Objectives: The multifaceted characteristic and task-specificity of postural control clearly reflects the need of knowing which factors could influence the balance measures in order to provide reliable and unbiased information. Therefore, this study aimed to investigate the effects of selected anthropometric characteristics, sex, lower limb`s strength and dominance on the Y balance test (YBT). Design: Descriptive laboratory study. Methods: Forty-two young adults performed the YBT. The raw and normalized reach distances values were recorded. ANOVA was used to examine differences between sex and limb dominance, whereas multiple linear regression models were built to identify variables associated with better postural control. Results: No significant sex differences were observed, except for the normalized anterior direction (p = 0.0324). No significant differences between limbs emerged. Regression models significantly explained between 8-49% of the variance. Trunk length, strength, and the interaction between sex with strength were the major predictors of the raw measures. Unexpectedly, lower limb length explained only 0.08% of the raw anterior direction variance. Strength and its interaction with sex were positively associated with normalized measures. Surprisingly, the relative lower limb length variable was negatively associated with the normalized measures. Each % point increase in relative lower limb length was associated with a decrease in normalized performance ranging from 1.73 to 4.91%. Conclusions: Anthropometric characteristics, sex and lower limb strength differently influenced the YBT measures, regardless of limb dominance. Consequently, these variables should be controlled to limit the variability for an accurate evaluation of postural balance, especially if different YBT measures are used.